Bioactive Glass and Silica Particles for Skeletal and Cardiac Muscle Tissue Regeneration - Ege, Duygu; Lu, Hsuan-Heng; Boccaccini, Aldo R. (Tissue Engineering - Part B: Reviews, 2024)
When skeletal and cardiac tissues are damaged, surgical approaches are not always successful and tissue regeneration approaches are investigated. Reports in the literature indicate that silica nanoparticles and bioactive glasses (BGs), including silicate bioactive glasses (e.g., 45S5 BG), phosphate glass fibers, boron-doped mesoporous BGs, borosilicate glasses, and aluminoborates, are promising for repairing skeletal muscle tissue. Silica nanoparticles and BGs have been combined with polymers to obtain aligned nanofibers and to maintain controlled delivery of nanoparticles for skeletal muscle repair. The literature indicates that cardiac muscle regeneration can be also triggered by the ionic products of BGs. This was observed to be due to the release of vascular endothelial growth factor and other growth factors from cardiomyocytes, which regulate endothelial cells to form capillary structures (angiogenesis). Specific studies, including both in vitro and in vivo approaches, are reviewed in this article. The analysis of the literature indicates that although the research field is still very limited, BGs are showing great promise for muscle tissue engineering and further research in the field should be carried out to expand our basic knowledge on the application of BGs in muscle (skeletal and cardiac) tissue regeneration.
CRIS-Team Scopus Importer:2024-03-08
Keywords: bioactive glass; borate glass; cardiac muscle; phosphate glasses; silica nanoparticles; skeletal muscle